Evaluation of factors affecting the quantity and quality of platelet-rich plasma and platelet-derived growth factor-BB - Rahul Verma; Priyanka Sharma; Gita Negi; Abhishek Kandwal; Harish Chandra (Wolters Kluwer Medknow Publications, 2021)
Context: Platelet-rich plasma (PRP) releases growth factors (GFs) upon activation which accelerates the healing and regeneration in the target tissue. Wider applications of PRP warrant product standardization. PRP compositions may vary according to the patient's demographics and the constituents of PRP. Aims: Our study aimed to assess the correlations between age, gender, platelet counts, platelet indices, platelet yield, platelet dose, GF dose, and platelet-derived GF-BB (PDGF-BB) concentration. Settings and Design: This was an experimental study done in the Department of Pathology along with the Department of Dentistry at a tertiary care hospital in North India. Subjects and Methods: PRP was prepared from 40 ml of whole blood. Platelet counts, platelet indices (LH 750 coulter analyzer, Florida, USA), and PDGF-BB levels (enzyme-linked immunosorbent assay, Qayee Bio., Ltd, China) were measured. Platelet yield (%), platelet dose (×106), and GF dose (×1012) in PRP were also calculated. Statistical Analysis Used: All the parameters were analyzed using Pearson's correlation coefficient and linear regression. Paired t-test and Mann-Whitney test were used for two-group analysis. Results: Mean platelet count, PDGF-BB concentration, platelet yield, platelet dose, and GF dose in PRP were 1317 × 103/mm3, 30 ± 9.89 ng/ml, 71.62 ± 28.34%, 6.5 ± 3.5 × 109, and 159.62 ± 52.39 ng/ml, respectively. PRP platelet counts were positively correlated with PDGF-BB concentration, platelet yield, platelet dose, and GF dose. Conclusions: Of all the parameters, PDGF-BB concentration, platelet yield, platelet dose, and GF dose showed a positive correlation with PRP platelet count. Age, gender, and platelet indices had no significant influence.